Exploring geometry and measurement in the Perjuangan Subkoss Garuda Sriwijaya Museum: An ethnomathematics study - Lisnani, Lisnani; Lestari, Natalia Putri; Suyono, Agus (Universitas Hamzanwadi, 2024)
The Museum of Perjuangan Subkoss Garuda Sriwijaya is a museum that preserves the history of South Sumatra’s struglle against the Dutch and Japanese colonialists. This research aims to obtain the results of an ethnomathematics study from the Museum of Perjuangan Subkoss Garuda Sriwijaya regarding historical, philosophical, and mathematical aspects and implement it in the Merdeka Curriculum in mathematics for elementary schools. This research employs an ethnographic approach with a qualitative descriptive approach, utilizing observation, interviews, documentation, field notes, and data triangulation. The analysis techniques include data reduction, data presentation, verification, and conclusions drawings. The study involved three informants who had direct interaction with the Museum of Perjuangan Subkoss Garuda Sriwijaya. The results of this research shows that ethnomathematics studies offer several insights: the historical aspect introduces local history and culture through artifacts that supported the struggle during the physical revolution; the philosophical aspectteaches the values ​​of caring, cooperation, creativity, and diversity within society; and the mathematical concepts reveals the concept of geometry, including area, perimeter, volume of both two-dimensional figures and three-dimensional figures, and length measurement.